Des obligations de diligence, de résultat et de garantie - Crépeau, Paul-André (Assurances)

(untitled) (HEC Montréal, 1990)
ln his article, the author illustrates the intensity of legal obligation by subdividing this obligation into three levels: the obligation of diligence, of result and of guarantee. ln doing so, Me Crépeau presents a concrete reflection on the basis of civil liability where what is important is not so much to determine if there is fault, but rather to accurately assess the content and intensity of the debitor's obligations.